FROM GUCCI TO GREEN BAGS: CONSPICUOUS CONSUMPTION AS A SIGNAL FOR PRO-SOCIAL BEHAVIOR. Issue 4 (2nd October 2018) - Johnson, Catherine M.; Tariq, Ayesha; Baker, Thomas L.
Abstract : Conspicuous consumption usually implies the purchase of luxury goods with the purpose of signaling wealth and status. Previous literature also treats conspicuous pro-social behaviors, such as donating to pro-social causes or buying green products, as instruments for signaling wealth. This study separates conspicuous consumption of pro-social products from signaling wealth and provides evidence that it can be motivated by need for status as well as a pro-social self-concept. Two separate studies show that fear of negative evaluation and salience of pro-social self-concept were found to moderate the effects of need for status and pro-social self-concept on the consumption of pro-social products.